The genomic landscape of relapsed infant and childhood KMT2A-rearranged acuteleukemia - Pilheden, Mattias; Hagström Andersson, Anna; Ahlgren, Louise; Sturesson, Helena; Singh, Varsha; Song, Guangchun; Walsh, Michael P.; Yang, Minjun; Castor, Anders; Pronk, Cornelis Jan; Zhao, Huanbin; Maillard, Maud; et al. (Lund University, 2024)
This dataset includes whole genome and whole exome sequencing of diagnostic, germline, and relapse samples of 21 infants and 12 children with relapsed ALL (n=21) or AML (n=12), and targeted deep sequencing of 258 samples taken during treatment for 30 infants or children with ALL or AML. All patients had an underlying rearrangement of the KMT2A gene

Whole genome and exome sequencing was performed using Illumina TruSeq Nano protocol. Targeted sequencing libraries was prepared using Nextera XT DNA Sample Preparation Kit (Illumina) and sequenced on the Illumina MiSeq.
Keywords: Sequence analysis; Cancer genetics; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi; Biological Sciences; Biologi